Evaluation Of The Implementation Of The 2020 Basic Life Support Guideline In Evacuation Of Natural Disaster Victims At The Forum Volunteer Sidoarjo Tough (Forest) - Winoto, Priyo Mukti Pribadi; Setiawan, Arif Helmi; Rohmawati, Riska (STRADA : Jurnal Ilmiah Kesehatan, 2021)
<p style="color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">This study aims to evaluate the application of the 2020 basic life support guidelines in the evacuation of victims of natural disasters by the Sidoarjo Tangguh Volunteer Forum (Forest). This research method uses a quantitative cross-sectional design that aims to photograph and analyze the situation at a certain time to evaluate the application of the 2020 basic life support guidelines in the evacuation of victims of natural disasters. The sample in this study was taken with a total sampling of 20 people. Methods of collecting data using primary data, through questionnaires and using a check list. Data processing was carried out by means of Wilcoxon sign rank test analysis. Basic Life Support can run well if all elements are carried out thoroughly, therefore it is necessary to have clear roles, duties and responsibilities from the management to support the success in evacuating victims of natural disasters at the Volunteer Forum